Association of aberrant ASNS imprinting with asparaginase sensitivity and chromosomal abnormality in childhood BCP-ALL - Watanabe, Atsushi (Blood, 2020)
Karyotype is an important prognostic factor in childhood B-cell precursor acute lymphoblastic leukemia (BCP-ALL), but the underlying pharmacogenomics remain unknown. Asparaginase is an integral component in current chemotherapy for childhood BCP-ALL. Asparaginase therapy depletes serum asparagine. Normal hematopoietic cells can produce asparagine by asparagine synthetase (ASNS) activity, but ALL cells are unable to synthesize adequate amounts of asparagine. The ASNS gene has a typical CpG island in its promoter. Thus, methylation of the ASNS CpG island could be one of the epigenetic mechanisms for ASNS gene silencing in BCP-ALL. To gain deep insights into the pharmacogenomics of asparaginase therapy, we investigated the association of ASNS methylation status with asparaginase sensitivity. The ASNS CpG island is largely unmethylated in normal hematopoietic cells, but it is allele-specifically methylated in BCP-ALL cells. The ASNS gene is located at 7q21, an evolutionally conserved imprinted gene cluster. ASNS methylation in childhood BCP-ALL is associated with an aberrant methylation of the imprinted gene cluster at 7q21. Aberrant methylation of mouse Asns and a syntenic imprinted gene cluster is also confirmed in leukemic spleen samples from ETV6-RUNX1 knockin mice. In 3 childhood BCP-ALL cohorts, ASNS is highly methylated in BCP-ALL patients with favorable karyotypes but is mostly unmethylated in BCP-ALL patients with poor prognostic karyotypes. Higher ASNS methylation is associated with higher L-asparaginase sensitivity in BCP-ALL through lower ASNS gene and protein expression levels. These observations demonstrate that silencing of the ASNS gene as a result of aberrant imprinting is a pharmacogenetic mechanism for the leukemia-specific activity of asparaginase therapy in BCP-ALL.